The liminal state of academic freedom: navigating corporatization in higher education - Haris Alibašić; Christopher L. Atkinson; Jamee Pelcher (Springer, 2024)
Abstract For decades, academic freedom and shared governance have stood as cornerstones of higher education in the United States, but these principles face unprecedented challenges. Recent developments point to a disturbing decline in these critical values, stirring debates on the future viability of the higher education system. This study delves into the problematic trajectory of modern higher education, spotlighting the rise of corporate practices within academic institutions, the swelling ranks of university administration, and the disproportionate weight given to student evaluations in assessing faculty. These factors have converged to push academia into an unstable transition, a liminal phase fueled by external and internal forces. This study examines the evolving landscape of academic freedom within the corporatized university model. Utilizing the concept of liminality, it explores the transitional challenges faced by academia in balancing traditional scholarly values with emerging market-driven paradigms, arguing that the corporatization of universities represents a liminal phase, wherein the identity and purpose of academic institutions are in flux, significantly impacting the notion of academic freedom. The shift toward a consumer-oriented ethos endangers the foundational principles of higher education, risking substituting educational substance with the mere transaction of educational services. The study concludes by issuing a call to action for all stakeholders in higher education to acknowledge and confront these detrimental trends, thereby safeguarding the principles of academic freedom, shared governance, and the educational system's overall integrity and dynamism.